The Influence of Solvability, Company Growth and Profitability on Divident Policy and Firm Value at LQ 45 Companies on the Indonesia Stock Exchange - Riyanti Riyanti; Azimah Hanifah (Journal of Accounting and Finance Management, 2021)
This study aims to analyze the effect of solvency, company growth and profitability as well as dividend policy on firm value at LQ 45 companies listed on the Indonesia Stock Exchange (BEI). This research is an associative quantitative study and uses secondary data. Population and sample. The population in this study are manufacturing companies in LQ 45 companies which are also listed on the Jakarta Islamic Index (JII) which are still listed on the Indonesia Stock Exchange for the period 2012-2016. There are 8 companies. Determination of the sample using nonprobability sampling technique, namely purposive sampling obtained by 5 companies registered in the period 2012-2016. The criteria are a) manufacturing companies that have been and are still listed on the Indonesia Stock Exchange for the period 2012-2016, b.) Manufacturing companies that publish financial reports for the period 2012-2016, c. Companies that have positive profits during the 2012-2016 period, d. Companies that have complete financial data calculate the variables in this study during the 2012-2016 period. The analysis method used is path analysis with pruning models. The results of this study concluded that solvency has a direct effect on dividend policy, profitability has a direct effect on dividend policy, company growth does not have a direct effect on dividend policy. Solvency does not have a direct effect on Firm Value, Profitability has a direct effect on Firm Value, Company growth has no direct effect on Firm Value, Dividend Policy has a direct effect on Firm Value, Solvency has a direct effect on Firm Value through Dividend Policy and Profitability has a direct effect on Firm Value through Policy dividends and company growth do not have a direct effect on firm value through dividend policy in LQ 45 companies.